Seed production and variety changing periods of spring barley in the FSBSI “ARC “Donskoy” - N. G. Chertkova; Yu. G. Skvortsova; T. I. Firsova; G. A. Filenko (Зерновое хозяйство России, 2020)
The current paper has presented the stages of variety changing and the results of four-year study (2016-2019) of spring barley varieties bred in different years by the farmers of the Center. The area occupied by spring barley in the Rostov region in 2016-2019 ranged from 315.12 to 406.41 thousand hectares, which was from 6.7 to 8.9% of the total arable land. The average productivity in the region for all the years studied was 2.3 t/ha, varying from year to year from 1.7 t/ha in the dry 2018 year to 2.8 t/ha in the most favorable 2017 year. The 2018 year was unfavorable in terms of climatic conditions, where the area under spring barley was almost 354 thousand hectares, and the gross yield was 601.8 thousand tons. The purpose of the work was to consider the periods of spring barley variety changing in primary seed production. The study was carried out on blackearth (chernozem) soils of the southern zone of the Rostov region at the FSBSI “Agricultural Research Center “Donskoy”. The varieties were sown in the spring at the time optimal for spring crops. The maximum productivity of many spring barley varieties in breeding plots exceeded 5.0 t/ha. In 2016-2019 in seed plots, there were sown such spring barley varieties as “Gris”, “Ratnik”, “Leon”, “Schedry”. The year of 2018 was unfavorable for these varieties, both in scientific departments and among agricultural producers in the Rostov region. The variety “Schedry” showed the lowest productivity (4.8 t/ha and 3.9 t/ha) and 1000 grain weight (45.0 g and 42.2 g) in both PIP-2 and OS-1. In the favorable year of 2017, the variety “Gris” showed the best results, namely 8.0 t/ha of productivity and 50.6 g of 1000 grain weight. The variety “Gris” was characterized with a stable high 1000 grain weight (on average 50 g) through all years. In different years the varieties “Ratnik” and “Leon” produced the best yields.